2018
DOI: 10.1016/j.ygyno.2017.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and toxicity of first-line methotrexate chemotherapy in low-risk postmolar gestational trophoblastic neoplasia: The New England Trophoblastic Disease Center experience

Abstract: This is one of the largest studies to comprehensively catalogue toxicities associated with 8-day MTX/FA and one-day MTX infusion. Although treatment-related adverse events were more frequent with 8-day MTX/FA, these were all self-limited and resolved with no long-term sequelae. Given this and its higher effectiveness, 8-day MTX/FA remains the treatment of choice at NETDC for patients with low-risk postmolar GTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 39 publications
7
41
0
Order By: Relevance
“…This may be attributed to the reduction in the adverse reactions of CF, which minimizes autoimmune responses and improves patient prognosis. Compared to treatment with MTX alone, cotherapy with MTX and CF significantly decreased resistance rates and adverse reactions (Maestá et al 2017). Randomized controlled trials have shown that the efficacy and adverse effects of MTX-FA were significantly lower than those of ACT-D in treating patients with low-risk GTN (Shobeiri et al 2014), which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 89%
“…This may be attributed to the reduction in the adverse reactions of CF, which minimizes autoimmune responses and improves patient prognosis. Compared to treatment with MTX alone, cotherapy with MTX and CF significantly decreased resistance rates and adverse reactions (Maestá et al 2017). Randomized controlled trials have shown that the efficacy and adverse effects of MTX-FA were significantly lower than those of ACT-D in treating patients with low-risk GTN (Shobeiri et al 2014), which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 89%
“…In a group of 13 patients receiving intermittent high-dose methotrexate (30–250 mg/kg), there were reported symptoms of generalised pruritus, burning, irritation and blurred vision 9. Generalised eye symptoms such as conjunctivitis, dry eyes and blepharitis were also noted in patients who received methotrexate as part of their chemotherapy regimen for postmolar gestational trophoblastic neoplasia 10. There is also a case report of internuclear ophthalmoplegia in a 26-year-old man after receiving intrathecal methotrexate for lymphoma 11.…”
Section: Resultsmentioning
confidence: 99%
“…Although adverse events were more frequent in 8-day MTX-FA regimen, these events were self-limited and recovered without long-term sequelae. 27 In a study reported by Berkowitz et al 88% of patients with low-risk GTN achieved CR with 8-day MTX-FA regimen. The CR rate was 90.2% in stage 1 patients while it was 68% in patients with low-risk metastatic disease.…”
Section: Discussionmentioning
confidence: 96%